STATISTICAL EVALUATION OF ENVIRONMENTAL FACTORS AND SOIL FERTILIZERS EFFECTS ON GARDEN PEA (Pisum sativum) PRODUCTION PARAMETERS - Sergiu Erich PALCU; Claudia MUREŞAN; Radiana-Maria TAMBA-BEREHOIU; Ciprian Nicolae POPA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of the paper was to determine the effects of environmental factors and soil fertilizers (Universol Blue and Ferticare I, applied for 3 weeks), upon production parameters of garden pea (Pisum sativum). In this regard, there were analysed: soil pH and soil temperature at the moment of sowing. The garden pea, Bördi variety, was randomly sown in early April, on 18 plots, which formed 6 experimental variants (three plots on variant). First variant V1 was the control. Variants V2, V3 and V4 have been fertilised with Universol Blue (337.5g; 421.875g; 506.25 g/variant), and V5, V6 have been fertilised with Ferticare I (540g; 607.5g/variant). After harvesting, there were determined the statistical estimates of the peashells number/variant, estimates of total peashells weight/variant and individual peashells weight/variant. The results showed that soil pH values were in the weak acid range, pH of variants V2, V3 and V4 being slightly more acidic (6.59) than pH of V5 and V6. Soil temperatures was between 6° and 7° C all over the plots. The number of peashells was increased in all variants, relative to the control (control and V3 exhibited a high variability 26.12%, respectively 21.77%). Ferticare I fertilizer was more effective than Universol Blue (938.17 vs. 907.89 peashells). The t values were insignificant between variants, concerning most parameters. The evolution of pH to alkaline domain and the increase in soil temperature, favored the increase in the total weight of peashells (r=0.789*, respectively r=0.882*). Fertilization have reduced the variability, caused by environmental conditions. The application of fertilizers did not increase the weight of peashells, but increased the total number of peashells.